Impact of lyophilized Lactobacillus salivarius DSPV 001P administration on growth performance, microbial translocation, and gastrointestinal microbiota of broilers reared under low ambient temperature - Blajman, Jesica (2017)
This study was undertaken with the aim of investigating the effects of dietary supplementation of probiotic strain Lactobacillus salivarius DSPV 001P on growth performance, microbial translocation, and gastrointestinal microbiota of broilers reared under low ambient temperature. Two hundred and forty, one-day-old male Cobb broilers were randomly distributed into two treatment groups, a probiotic group and a control group, with four replicates per treatment and 30 broilers per replicate. The temperature of the broiler house was maintained at 18–22 °C during the first three weeks, after which the temperature was at range of 8 °C to 12 °C. The results showed that probiotic treatment significantly improved body weight of broilers when compared with the control group. After 42 days, the weight means were 2905 ± 365.4 g and 2724 ± 427.0 g, respectively. Although there were no significant differences, dietary inclusion of L. salivarius tended to increase feed intake and to reduce feed conversion ratio during the six-week experimental period. Similarly, supplementation tended to reduce the rate of mortality, with 12 deaths occurring in the probiotic group, and 20 in the control group. However, no differences were observed in intestinal bacterial concentrations of Enterobacteriaceae, E.coli, and lactic acid bacteria in both crop and caecum among treatments. Through our study, it appears that L. salivarius DSPV 001P was non-pathogenic, safe and beneficial to broilers, which implies that it could be a promising feed additive, thus enhancing the growth performance of broilers and improving their health.